Influence and safety of electronic apex locators in patients with cardiovascular implantable electronic devices: a systematic review. Issue 1 (1st January 2019) - AlRahabi, Mothanna K.; Ghabbani, Hani M.
ABSTRACT: The widespread use of cardiovascular implantable electronic devices has increased concerns regarding using electronic apex locators in patients with these devices. This systematic review investigated the effects and safety of using electronic apex locators in patients with cardiovascular implantable electronic devices. Methods : An electronic search in the Cochrane Library, PubMed (MEDLINE), ScienceDirect, and Scientific Electronic Library Online (Scielo) databases for relevant articles published between December 2000 and December 2018 was performed. The search strategy centered on terms related to electronic apex locators use during root canal treatment in patients with cardiovascular implantable electronic devices. Results : Seven studies (five in vitro and two in vivo ) fulfilled the inclusion criteria for this review. It was found that electronic apex locators can be used safely in patients with cardiovascular implantable electronic devices, when general precautions are followed. Conclusions : Although the present review suggests that electronic apex locators can be used safely in patients with implantable cardioverter defibrillators, consultation with patients' cardiologists remains advisable.